Efficient synthesis of C 2v-Symmetrical Pentakisadducts of C 60 as versatile building blocks for fullerene architectures that involve a mixed octahedral addition pattern - Hörmann, Frank; Donaubauer, Wolfgang; Hampel, Frank; Hirsch, Andreas (Chemistry - A European Journal, 2012)
We report here on the selective synthesis of fullerene pentakisadducts 3 with an incomplete octahedral addition pattern by means of mixed [5:1]hexakisadducts 1 that involve an isoxazoline moiety as a protection group. The isoxazoline addend can be cleanly cleaved by irradiation with light. By using this protection-deprotection strategy, a variety of fullerene pentakisadducts 3 were synthesized in 29-44 % overall yield without the need of HPLC purification. This novel photolytic deprotection of 1 can be explained by an initial electron transfer that leads to a biradical, which can easily eliminate the isoxazoline added. The very efficient and straightforward syntheses of the bisfullerene 4 and the globular hexakisadduct 7, each of which involves mixed octahedral addition patterns, clearly demonstrate the advantage of fullerene pentakisadducts 3 as suitable precursors for the construction of highly functional and complex [5:1]hexakisadduct architectures. Complete structural characterization of all new compounds was carried out by MALDI mass spectrometry, UV/Vis, FTIR, H NMR and C NMR spectroscopy, as well as X-ray diffraction. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.